PENERAPAN KEGIATAN MGMP GUNA MENINGKATKAN KEMAMPUAN PENGGUNAAN MEDIA PEMBELAJARAN DAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER PROSES PEMBELAJARAN - Nelson Tambunan (JURNAL PENA EDUKASI, 2020)
Abstract: This research is a school action research, with the research subjects of 16 teachers of SMA Negeri 2 Lintongnihuta. The object in this study is the result of the assessment of the ability of teachers in the use of learning media and the school environment as a source of learning in the teaching and learning process through the eye teacher deliberation activity. The instrument used was the Observation Sheet. Based on the results of the assessment, the number of teachers in cycle I who have been able to use learning media and the school environment as a learning resource in the "good" minimum category is 10 teachers or 62.50%, while the number of teachers in cycle II who are able to use it Learning media and the school environment as a source of learning in the "good" minimum category were 15 teachers or 93.75%. From the results of cycle I and cycle II actions, through the Implementation of Subject Teacher Deliberative Activities, it can improve the ability of teachers to use learning media and the learning resource school environment at SMA Negeri 2 Lintongnihuta for the 2018/2019 Academic Year.Keywords: learning media; learning resources; school environmentAbstrak: Penelitian ini merupakan penelitian tindakan sekolah, dengan subjek penelitian guru SMA Negeri 2 Lintongnihuta yang berjumlah 16 orang. Objek dalam penelitian ini adalah hasil penilaian Kemampuan Guru Dalam Penggunaan Media Pembelajaran Dan Lingkungan Sekolah Sebagai Sumber Belajar Dalam Proses Belajar Mengajar Melalui Kegiatan Musyawarah Guru Mata. Instrumen yang digunakan adalah Lembar Observasi. Berdasarkan hasil penilaian Jumlah guru pada siklus I yang telah mampu dalam penggunaan media pembelajaran dan lingkungan sekolah sebagai sumber belajar yang berada pada kategori minimal â€œbaikâ€ sebanyak 10 orang guru atau sebesar 62,50 %, sementara Jumlah guru pada siklus II yang mampu dalam penggunaan media pembelajaran dan lingkungan sekolah sebagai sumber belajar pada kategori minimal â€œbaikâ€ sebanyak 15 orang guru atau sebesar 93,75%. Dari hasil tindakan siklus I dan siklus II maka melalui Penerapan Kegiatan Musyawarah Guru Mata Pelajaran dapat meningkatkan kemampuan guru dalam penggunaan media pembelajaran dan lingkungan sekolah sumber belajar di SMA Negeri 2 Lintongnihuta Tahun Pelajaran 2018/2019.Kata kunci: lingkunngan sekolah; media pembelajaran; sumber belajar